Effect of Promotional Mix And Price On Consumer Subscription Decisions Mediated By Trust In Indihome Consumers In Medan (Emperis Study On Pt. Telkom Witel Medan) - Adika Fajar Putra; Lubis, Muhammad Arif (TALENTA Publisher, Universitas Sumatera Utara, 2021)
Indihome is a result of PT. Telkom. This examination means to analyze the impact of Promotion Mix (X1) and Price (X2) on Decision (Y) interceded by Trust (Z) Indihome Customers at PT Telkom Witel around there. Tests were taken upwards of 85 Indihome clients in Medan City utilizing an underlying condition model (Structural Equation Model). Information assortment utilized a poll while information investigation utilized Structural Equation Modeling (SEM) with Smart Partial Least Square (Smart PLS) adaptation 3.0 M3 programming. Test outcomes: 1. Advancement Mix significantly affects Consumer Decisions to buy in to Indihome in, 2. Costs significantly affect Consumer Decisions to buy in to Indihome, 3. Advancement Mix significantly affects Indihome Customer Confidence, 4. Costs significantly affect Indihome Consumer Confidence, 5. Trust significantly affects Consumer Decision to buy in to Indihome.